Targeted Intraoperative Radiotherapy Tumour Bed Boost during Breast-Conserving Surgery after Neoadjuvant Chemotherapy - a Subgroup Analysis of Hormone Receptor-Positive HER2-Negative Breast Cancer - Kolberg, Hans-Christian; Loevey, Gyoergy; Akpolat-Basci, Leyla; Stephanou, Miltiades; Fasching, Peter; Untch, Michael; Hoffmann, Oliver; Bulsara, Max; Vaidya, Jayant S.; Liedtke, Cornelia (Breast Care, 2017)
Introduction: In a previous study our group showed a beneficial effect of targeted intraoperative radiotherapy (TARGIT-IORT) as an intraoperative boost on overall survival after neoadjuvant chemotherapy (NACT) compared to an external boost (EBRT). In this study we present the results of a detailed subgroup analysis of the hormone receptor (HR)-positive HER2-negative patients. Methods: In this cohort study involving 46 patients with HR-positive HER2-negative breast cancer after NACT, we compared the outcomes of 21 patients who received an IORT boost to those of 25 patients treated with an EBRT boost. All patients received whole breast radiotherapy. Results: Median follow-up was 49 months. Whereas disease-free-survival and breast cancer-specific mortality were not significantly different between the groups, the 5-year Kaplan-Meier estimate of overall mortality was significantly lower by 21% with IORT, p = 0.028. Non-breast cancer-specific mortality was significantly lower by 16% with IORT, p = 0.047. Conclusion: Although our results have to be interpreted with caution, we have shown that the improved overall survival demonstrated previously could be reproduced in the HR-positive HER2-negative subgroup. These data give further support to the inclusion of such patients in the TARGIT-B (Boost) randomised trial that is testing whether IORT boost is superior to EBRT boost.
EVALuna2:36209